Extrahepatic metabolism at the body's internal–external interfaces. (August 2014) - Gundert-Remy, Ursula; Bernauer, Ulrike; Blömeke, Brunhilde; Döring, Barbara; Fabian, Eric; Goebel, Carsten; Hessel, Stefanie; Jäckh, Christine; Lampen, Alfonso; Oesch, Franz; Petzinger, Ernst; Völkel, Wolfgang; et al.
Abstract In general, xenobiotic metabolizing enzymes (XMEs) are expressed in lower levels in the extrahepatic tissues than in the liver, making the former less relevant for the clearance of xenobiotics. Local metabolism, however, may lead to tissue-specific adverse responses, e.g. organ toxicities, allergies or cancer. This review summarizes the knowledge on the expression of phase I and phase II XMEs and transporters in extrahepatic tissues at the body's internal–external interfaces. In the lung, CYPs of families 1, 2, 3 and 4 and epoxide hydrolases are important phase I enzymes, while conjugation is less relevant. In skin, phase I-related enzymatic reactions are considered less relevant. Predominant skin XMEs are phase II enzymes, whereby glucuronosyltransferases (UGT) 1, glutathione-S-transferase (GST) and N-acetyltransferase (NAT) 1 are important for detoxification. The intestinal epithelium expresses many transporters and phase I XME with high levels of CYP3A4 and CYP3A5 and phase II metabolism is mainly related to UGT, NAT and Sulfotransferases (SULT). In the kidney, conjugation reactions and transporters play a major role for excretion processes. In the bladder, CYPs are relevant and among the phase II enzymes, NAT1 is involved in the activation of bladder carcinogens. Expression of XMEs is regulated by several mechanisms (nuclear receptors, epigenetic mechanisms, microRNAs). However, the understanding why XMEs are differently expressed in the various tissues is fragmentary. In contrast to the liver – where for most XMEs lower expression is demonstrated in early life – the XME ontogeny in the extrahepatic tissues remains to be investigated.